NMR spin-spin coupling constants and hyperconjugative interactions - Contreras, Ruben Horacio (2010)
The potential of NMR spin-spin coupling constants as probes to study fine details of electronic molecular structures is briefly discussed in this work through two different examples. A qualitative analysis of the polarization propagator expression for the Fermi contact term is applied for predicting factors affecting 1JCH, and comments are made about how to generalize those results to different types of one-bond spin-spin couplings. Moreover, the Natural J Coupling method is applied to get insight into electronic factors defining a. Karplus relationship of type 3J HH (180°) < 3JHH(0°) known in the literature for some amino acids. © 2009 Wiley Periodicals, Inc.